ISPC Assessment of Flagship 5: Livestock, Livelihoods and Agri-Food Systems - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
ISPC Assessment of Flagship 5 (Livestock, livelihoods and agri-food Systems) of the CGIAR Research Program on Livestock Agri-Food Systems (2017-2022). The objective of this FP is to ensure that the technologies and strategies developed by this CRP translate into positive impacts on the welfare of the resource poor, in particular women.